An economic vision of the border development between Tulcán and Ipiales during the period 2018-2019 - López Cadena, Julio Iván; Jiménez Montalvo, Daniel Andrés (SATHIRI, 2022)
The research process focused on the macroeconomic analysis between Ecuador and Colombia in the years 2018-2020, as an alternative to the Tulcán-Ipiales border development, within the studied in the two countries there are aspects that condition almost similar results, and in subordination to macroeconomic indicators can be noted the economic-trade aspect is essential between the two border cities. This is mainly based on the commercial activity of goods and services and whose profit is tied to the fluctuation of the exchange rate of the US dollar vs the Colombian peso and because of the current conditions on the border this activity favors in some way measure to the city of Ipiales, Despite being closed the international bridge of Rumichaca since March 2020. Complementary to the above the issue of the Covid-19 pandemic is significantly affectingthe commercial activity of certain sectors in the two border cities. In virtue of this, it isnecessary to contribute to the economic reactivation in the frontier development to propose several strategies that go from the sense of rethinking new and innovative business models for the companies located in the border, the necessary support of the national government through public policies, and necessary subsidies for certain productive sectors, until promoting the potentialization of electronic commerce that in this time has given much result.